Kebijakan Vaksinasi COVID-19 di Indonesia: Sebuah Upaya Dalam Meningkatkan Partisipasi Masyarakat Untuk di Vaksin - Hamdan Hamdan; Roni Ekha Putera (Jurnal Administrasi Publik dan Pembanguan, 2023)
The government has started the COVID-19 vaccination program in Indonesia, on January 13, 2021, targeting 70% of Indonesia's population. However, in implementing the COVID-19 vaccination nationally, there are various obstacles, such as many people who are afraid of the side effects of vaccines, halal vaccines and paid vaccinations which are rejected by the community. The low level of public confidence in the COVID-19 vaccine is further exacerbated by hoax news about vaccines that are spreading in the community. The purpose of this study is to see how the policies taken by the Indonesian government in increasing public participation for the COVID-19 vaccine. The research method used in this study uses a literature review research method with a qualitative approach. The results of the study show that the Indonesian government's policy in an effort to increase public participation for the COVID-19 vaccine is to apply a COVID-19 vaccine certificate as a requirement in public activities. The use of the COVID-19 vaccine certificate has increased public participation in the vaccine. In addition, the behavior of public officials showing that the COVID-19 vaccine is safe to use after being vaccinated has also increased public participation in the Covid-19 vaccine.